2006
DOI: 10.1128/jcm.00443-06
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Reverse Transcription-PCR Assay for Detection of Norovirus Genogroup I

Abstract: We have developed a one-tube reverse transcription (RT)-PCR method using the real-time TaqMan PCR system for the detection of norovirus genogroup I (NV GGI). By introduction of a novel probe based on locked nucleic acid technology, we enhanced the sensitivity of the assay compared to those of conventional TaqMan probes. The sensitivity of the NV GGI RT-PCR was determined by probit analysis with defined RNA standards and quantified norovirus isolates to 711 copies/ml (95% detection limit). In order to detect PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 31 publications
2
21
0
2
Order By: Relevance
“…These limitations were addressed with the development of real-time RT-PCR for norovirus diagnostics. These assays used numerous detection methods, including SYBR green (190)(191)(192)(193), hydrolysis (TaqMan) (194)(195)(196)(197)(198)(199)(200)(201)(202), and hybridization probes (203,204). While many of these assays were directed at the viral polymerase gene, further sequence analysis revealed that a conserved region at the ORF1-ORF2 polymerase-capsid junction could also be used as an effective target for detection.…”
Section: Molecular Diagnostic Testsmentioning
confidence: 99%
“…These limitations were addressed with the development of real-time RT-PCR for norovirus diagnostics. These assays used numerous detection methods, including SYBR green (190)(191)(192)(193), hydrolysis (TaqMan) (194)(195)(196)(197)(198)(199)(200)(201)(202), and hybridization probes (203,204). While many of these assays were directed at the viral polymerase gene, further sequence analysis revealed that a conserved region at the ORF1-ORF2 polymerase-capsid junction could also be used as an effective target for detection.…”
Section: Molecular Diagnostic Testsmentioning
confidence: 99%
“…La introducción del diagnóstico empleando RPC en tiempo real ha sido de gran importancia para mejorar el diagnóstico y establecer el rol relevante de NoV en brotes epidémicos agudos y en casos esporádicos de diarrea. Este método diagnóstico ha permitido demostrar la amplia heterogeneidad y rápida evolución de las variantes genéticas de NoV 8,9,[11][12][13][14][15] ; La diversidad antigénica y la falta de sistema de cultivo in vitro del virus mantendrá al diagnóstico molecular como el mejor método de detección de NoV. La RPC a tiempo real ha emergido como el estándar para el diagnóstico y detección de NoV, ya que combina un alto rendimiento, reproducibilidad, sensibilidad y especificidad 11,27,[42][43][44][45][46] . El 36,6% de los pacientes en este estudio fueron ingresados al hospital con un diagnóstico diferente al de una gastroenteritis, adquiriendo la infección probablemente en forma nosocomial (plazo de latencia para los síntomas de 3 o más días), siendo mayor para NoV (32,1%) que para RV (5,7%).…”
Section: Discussionunclassified
“…There are two major groups of sequence-specific oligonucleotide probes: hydrolysis (e.g., TaqMan) probes and hybridization probes (e.g., molecular beacons and fluorescence resonance energy transfer probes); both groups are homologous to the internal region of amplified products. TaqMan probes have been frequently used in RT-qPCR for detecting hNOVs [67][68][69][70][71][72][73]. While RNA polymerase and capsid genes are the primary targets for amplification, within the NoV genomes, a junction of ORF1-ORF2-polymerase-capsid has been demonstrated to be the most highly conserved region that can serve as an effective target for amplification.…”
Section: Quantitative Real Time Rt-pcr (Rt-qpcr)mentioning
confidence: 99%